Box Cooler Design on Duku Fruit Alcohol Distillation Machine with refrigerator cooling system - Ahmad Akromul Huda; Karyanik Karyanik; Muanah Muanah; Earlyna Sinthia Dewi (Universitas Muhammadiyah Mataram, 2025)
This research aims to design and build an alcohol distillation machine made from duku fruit using a refrigerator cooling system and a box cooler as a condenser. The distillation machine utilizes a heating furnace to produce ethanol vapor from fermentation, which is then condensed in a cooled box cooler. Tests were conducted with variations in furnace temperature (110°C, 125°C, 140°C, and 155°C). The results show that the higher the heating temperature, the volume of distillate produced increases, from ±132 ml to ±330 ml. However, the ethanol content remained relatively low (10-20%) due to the low initial ethanol content of the fermentation and only one-stage distillation. These results show that the design of the device can function well on a laboratory scale, although further distillation is needed to increase the ethanol content. This research is expected to be the first step in developing a small-scale ethanol distillation device that is efficient and easy to implement.